Integrated physiological, transcriptomic, and metabolomic analyses of drought stress alleviation in Ehretia macrophylla Wall. seedlings by SiO2 NPs (silica nanoparticles) - Chen, Minghui; Jiao, Si-qian; Xie, Lihua; Geng, Xining; Qi, Shuaizheng; Fan, Jianmin; Cheng, Shiping; Shi, Jiang; Cao, Xibing (Frontiers in Plant Science, 2024)
With environmental problems such as climate global warming, drought has become one of the major stress factors, because it severely affects the plant growth and development. Silicon dioxide nanoparticles (SiO2 NPs) are crucial for mitigating abiotic stresses suffered by plants in unfavorable environmental conditions and further promoting plant growth, such as drought. This study aimed to investigate the effect of different concentrations of SiO2 NPs on the growth of the Ehretia macrophylla Wall. seedlings under severe drought stress (water content in soil, 30–35%). The treatment was started by starting spraying different concentrations of SiO2 NPs on seedlings of Ehretia macrophyla, which were consistently under normal and severe drought conditions (soil moisture content 30-35%), respectively, at the seedling stage, followed by physiological and biochemical measurements, transcriptomics and metabolomics analyses. SiO2 NPs (100 mg·L−1) treatment reduced malondialdehyde and hydrogen peroxide content and enhanced the activity of antioxidant enzymes under drought stress. Transcriptomic analysis showed that 1451 differentially expressed genes (DEGs) in the leaves of E. macrophylla seedlings were regulated by SiO2 NPs under drought stress, and these genes mainly participate in auxin signal transduction and mitogen-activated protein kinase signaling pathways. This study also found that the metabolism of fatty acids and α-linolenic acids may play a key role in the enhancement of drought tolerance in SiO2 NP-treated E. macrophylla seedlings. Metabolomics studies indicated that the accumulation level of secondary metabolites related to drought tolerance was higher after SiO2 NPs treatment. This study revealed insights into the physiological mechanisms induced by SiO2 NPs for enhancing the drought tolerance of plants.